(untitled) (Tempo e Argumento, 2021)
This article focuses on the emergence and the first years of an unprecedented association of organized fans in the state of São Paulo, ATOESP, which existed during the 1970s. From interviews, sources from the period’s press and taking as the reference framework English Marxist historiography, notably, E. P. Thompson’s works, the conditions for the existence of this entity are analyzed, one that emerged amid São Paulo’s professional football set of that historical period, during the height of Brazil’s civil-military dictatorship. It is shown how, despite the commonsense view about rivalries between supports, the leaders of the groupings gathered in the Association cultivated closeness, dialogue and even friendship relationships that made its conformation possible. The social experience that went beyond the domains of football is thus highlighted, since it fed from the participation of leaders and their groups in the sociability of São Paulo’s carnival blocks and samba schools. Next, the agenda of claims is described and analyzed, which, in the second half of the 1970s, led to the call by ATOESP for boycotts and acts against measures adopted by the São Paulo Football Federation regarding the sports calendar and the increase in ticket prices. Finally, the main part of the article focuses on both the growing feuds between the base of organized fans from 1976 onwards —which includes the use of white arms in stadium facilities— and the conflicts between fans and the Military Police (PM). If there is a need to articulate the representatives of these associations with the PM in logistics and organization of matches, the escalation of incidents between fans and police officers at the end of that decade, as reported by the media and remembered by interviewees, gave the unifying tonic to the collective actions of ATOESP until the beginning of the 1980s, when the redemocratization of civil life is placed on the national political horizon Keywords: football history in Brazil; football organized fans; sports journalism; São Paulo state; 1970’.